PENGEMBANGAN ASESMEN KETERAMPILAN BERPIKIR KREATIF MAHASISWA PADA MATERI ANALISIS DAMPAK-DAMPAK GLOBALISASI - Purba, Jon Roi; Siagian, Asister; Silalahi, Dumaris (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2023)
The aim of this development research is to develop an assessment of student's creative thinking skills on material analyzing the impacts of globalization. The assessment consists of a number of essay questions about students' creative thinking skills with indicators such as the ability to think fluently (fluency), think flexibly (flexibility), think originality (originality), and think elaboration (elaboration). The type of research is development with a 4D model which consists of 4 stages, namely define, design, develop and disseminate. The test subjects were 40 elementary school teacher education study program students in Pematangsiantar. The assessment of creative thinking skills involves experts, including creative thinking experts, learning experts, and social science content experts (criticizing the depth and correctness of the material). Experts validate the content, assess the product and student response questionnaires. The results of this research are assessments that have been validated and received advice from experts as validators, revised and tested again until calculated using CVR and CVI calculations, thus the validity results of students' creative thinking skills questions are declared valid and can be used as an assessment of thinking skills. creative in material analyzing the impacts of globalization